Técnica de vibração de língua: aspectos do aprendizado, dos efeitos acústicos e das imagens do trato vocal e da face - Bueno, Thais da Costa (2006)
Voice therapy techniques are used by voice clinics so as to soothe or eliminate vocal complaints. The voiced tongue vibration technique is one of the most used techniques in the voice clinic. Therefore, it is considered a universal technique. However this technique can be not so accurately applied and/or performed by the patient at times. The purpose of this study was to analyze the voiced tongue vibration technique of 20 female speech pathologist with a minimum 5 year voice clinic practice with no vocal complaint or voice disorder. The following parameters were analyzed: (1) clinical practice; (2) vocal tract visual image (postural, facial, and vocal tract structures images during 1minute and half of voiced tongue vibration technique); (3) acoustics outcomes (perceptual and acoustic analysis). The subjects answered 2 different protocols, one regarding professional experience and the other one about specific learning on the voiced tongue vibration technique. Digital recording was performed on the subjects prior to and following 1 minute and half of voiced tongue vibration technique in the speaking fundamental frequency during the fiber optic videolaringoscopy recording. The recording material consisted of: date, sustained vowel /a/ and /e/, days of the week and a sentence from CAPE-V translated phonetically into Portuguese - Minha mãe namorou um anjo . In the same time it was videotaped the posture and faces of the subjects during the technique performance. The study data was analyzed by trained listeners. The data underwent statistic analyses. The results showed that SLP specialized in the voice area tend to have a continuous improvement on the voiced tongue vibration technique through specialization courses, masters, and PhDs. The results also indicated that the SLP first learn the technique in college and that they only affirm to have absolute control on the technique when the patients start to show voice improvement. Most of the SLP believe that the main goal of the technique is to enhance mucosal wave and improve glotic closure. Most SLP select the technique for nodule treatment which can show that the technique selection is still based on the ENT diagnosis and not on the vocal features. The use of voiced tongue vibration technique in speaking fundamental frequency presented no impact on pitch. Results also showed that after the technique performance hard glottal attack was milder and voice quality got worse in some cases, maybe due to mucus enhance caused by the fiber optic laryngoscopy examination. The vocal tract presented anterior-posterior pharyngeal constriction during technique. There was no amplification of the pharynx nor vestibular vocal folds medialization or vibration. Nevertheless, results indicated a whole vibration of the larynx box and lowering of the larynx in some of the subjects, maybe due to a subtle change on the fundamental frequency during the technique. Vocal folds were rarely visualized during the technique due to supraglottic constriction. However 11 subjects presented incomplete vocal fold closure. There is no relation between head/neck/face posture change and the vocal tract behavior. The acoustic analysis showed no change in the fundamental frequency after the technique performance (11 subjects). Data showed that there was enhancement of harmonics and significant improvement on the spectrographic trace. Regarding vocal tract behavior, more specifically to glottic closure, the study concluded that the findings of this research differ from the literature. However the perceptual and acoustic analysis indicated similar results with the literature specially related to noise-to-harmonic ratio